2018
DOI: 10.21037/jtd.2018.03.64
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate lymphadenectomy significantly reduced recurrence after segmentectomy for patients with non-small cell lung cancer

Abstract: Background: Segmentectomy has been widely used for small-sized non-small cell lung cancer (NSCLC).The objective of this study is to determine the impact of number of harvested lymph nodes (LNs) on survival for patients undergoing segmentectomy. Methods: The clinicopathologic data of patients undergoing segmentectomy for NSCLC from July 2011 to December 2014 were retrospectively analyzed. Survival analysis was performed by Kaplan-Meier method and Cox regression analysis. Results: A total of 259 patients with NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…One can even say that the level of exigency should be even higher because of the potential for overlooking iLNs. This leads us to make the following recommendations, which are not our own but those inspired by surgeons and expert centers that have been cited in this article ( 11 , 17 , 18 , 23 , 26 , 27 , 29 , 40 ):…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One can even say that the level of exigency should be even higher because of the potential for overlooking iLNs. This leads us to make the following recommendations, which are not our own but those inspired by surgeons and expert centers that have been cited in this article ( 11 , 17 , 18 , 23 , 26 , 27 , 29 , 40 ):…”
Section: Discussionmentioning
confidence: 99%
“…In 259 patients who underwent segmentectomy for NSCLC, Huang et al showed that when patients had more than 6 nodes examined, the rate of diagnosed lymph node metastases was significantly higher (9.4 vs. 1.5%, p = 0.005) and 5-year survival was significantly higher ( 27 ). In Yendamuri's series of 3,916 patients operated on for stage I NSCLC by SLR, the only prognostic factor in multivariate analysis for 5-year survival was the number of nodes examined, while the extent of resection did not have a significant influence ( 28 ).…”
Section: The Influence Of the Number Of Nodes Removed On Survivalmentioning
confidence: 99%
“…In addition, some patients who had no intersegmental lymph node clearance can be understaged and do not benefit from an adjuvant treatment. (22).…”
Section: Intersegmental Lymph Nodes Analysismentioning
confidence: 99%
“…A more recent comparative study has shown an increased risk of recurrence in patients undergoing sublobar resection compared to patients who underwent lobectomy (8). An argument that has been suggested to explain this result is that the lymphadenectomy during such operations is frequently insufficient, although it is widely demonstrated that an inadequate lymphadenectomy is a major factor for recurrence (9).…”
mentioning
confidence: 99%